A Rare Cause of Pain in a Patient Following Roux-en-Y Choledochojejunostomy - Kristiana Sather; Matthew Wheelwright; Guru Trikudanathan; Gregory Beilman (Case Reports in Surgery)
Introduction. Sump syndrome is a rare complication following bilioenteric anastomosis, most commonly following choledochoduodenostomy. This is only the third case in the literature of sump syndrome of the distal common bile duct (CBD) following end-to-side Roux-en-Y choledochojejunostomy (RYCJ). Case Presentation. A 69-year-old man with a history of end-to-side RYCJ for recurrent primary choledocholithiasis presented 3 years postoperatively with right upper quadrant (RUQ) abdominal pain affecting his quality of life. The work up revealed mild leukocytosis and computed tomography (CT) imaging that showed dilation of the distal CBD remnant. He underwent endoscopic retrograde cholangiopancreatography (ERCP) with the removal of large amounts of debris with initial resolution of his pain, but the pain recurred after several months and after two further ERCPs with only short-term resolution of pain, he eventually underwent an open distal CBD excision and the pain has since resolved. Conclusions. This case report describes a rare case of sump syndrome following RYCJ that presented with abdominal pain alone. Sump syndrome may have a wide array of presenting symptoms, and the pathophysiology of sump syndrome varies based on bilioenteric reconstruction. Although it has rarely been reported to occur in the distal blind CBD remnant following either RYCJ or hepaticojejunostomy, it is important to consider this in the differential for patients with abdominal pain following any bilioenteric reconstruction.